1995
DOI: 10.1039/c39950001005
|View full text |Cite
|
Sign up to set email alerts
|

Base and acid catalysis by the alkali-containing MCM-41 mesoporous molecular sieve

Abstract: Sodium and caesium cation-exchanged mesoporous MCM-41 are shown t o be mild, selective, water-stable and recyclable catalysts for the base-catalysed Knoevenagel condensation and acid-catalysed acetalization and aldol condensation, whereas caesium acetate-impregnated MCM-41 shows strong base activity in the Michael addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 9 publications
2
93
1
2
Order By: Relevance
“…• C and 665 All the structures of the isolated products 3a-e and 4a-j were elucidated using IR, 1 H NMR, 13 C NMR, and MS analyses. The IR showed a characteristic band for OH group for 3a-e products, which was not recorded for products (4a-j).…”
Section: Co 2 -Temperature Programmed Desorption (Co 2 -Tpd)mentioning
confidence: 99%
See 1 more Smart Citation
“…• C and 665 All the structures of the isolated products 3a-e and 4a-j were elucidated using IR, 1 H NMR, 13 C NMR, and MS analyses. The IR showed a characteristic band for OH group for 3a-e products, which was not recorded for products (4a-j).…”
Section: Co 2 -Temperature Programmed Desorption (Co 2 -Tpd)mentioning
confidence: 99%
“…Heterogeneous catalysis induced by solid catalysts such as basic alumina [11], alumina-KF [12] and homogeneous phase transfer catalysis with surfactants [13] in bi-phase system, the two divergent approaches being explored are aimed at achieving higher atom selectivity. The solid base catalysts provide an alternative to the classical soluble bases with emphasize to avoid the environmental problems caused by salt formation and hazardous conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Tolman et al [4] and we [5] have reported some low molecular weight, structurally characterized Cu II ± phenolate complexes that can be chemically or electrochemically oxidized to generate relatively stable Cu II -phenoxyl species. [6] These complexes are EPR-silent; they possess a diamagnetic (S 0) ground state.…”
mentioning
confidence: 89%
“…Many kinds of mesoporous silicalites have been identified to be lamella, hexagonal, and cubic phases, in which the pores possess high regular arrays in the 1.5-10 nm size range, depending on the template used [2,[6][7][8]. The mesoporous materials are known to offer new opportunities for their applications in catalysis, chemical separation, adsorption media, supports, ion-exchangers, host systems, and advanced composite materials [9][10][11][12][13][14][15][16][17][18][19]. The structures and the properties of mesoporous materials can be diversely adjusted by a sophisticated choice of organic templates, reaction parameters, and auxiliary cationic framework sources [1,6,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%